Correlation of Short Axial Axis of the Eyeball with Visual Outcome Post-Cataract Operation - Azelya Rindu Irmafesya; Dedeh Kurniasih; Dewi Karita; Prima Maharani Putri (LifeSciFi, 2026)
Cataract is a leading cause of visual impairment that can be treated surgically. Surgical success depends not only on technique but also on ocular anatomical factors, including axial length. A short axial axis may reduce the accuracy of intraocular lens power calculation. This study aims to analyze the correlation between short axial axis and postoperative visual outcomes after cataract surgery. An analytical observational study with a cross-sectional design was conducted using secondary data from medical records of senile cataract patients who underwent phacoemulsification. Subjects had an axial length <22 mm and documented postoperative visual acuity at least one month after surgery. Visual acuity was converted to logMAR units and analyzed using appropriate correlation tests. The study included 84 cataract patients with a median axial length of 21.57 mm. Postoperative visual acuity improved compared with preoperative values. Spearman correlation analysis revealed a significant association between short axial length and postoperative visual outcomes (r = 0.27; p = 0.01), indicating a weak positive correlation and suggesting that visual outcomes are influenced by multiple factors beyond axial length alone. These findings highlight the importance of comprehensive preoperative assessment to optimize visual outcomes following cataract surgery.